2004
DOI: 10.1007/s00359-004-0572-x
|View full text |Cite
|
Sign up to set email alerts
|

Gliding behaviour elicited by lateral looming stimuli in flying locusts

Abstract: We challenged tethered, flying locusts with visual stimuli looming from the side towards one eye in a way that mimics the approach of a predatory bird. Locusts respond to the lateral approach of a looming object with steering movements and a stereotyped, rapid behaviour in which the wingbeat pattern ceases and the wings are swept into a gliding posture. This gliding behaviour may cause the locust to dive. The gliding posture is maintained for 200 ms or more after which flight is resumed with an increased wingb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(146 citation statements)
references
References 41 publications
13
129
2
Order By: Relevance
“…They found that the DCMD neuron's peak spike rate occurs with a constant delay after the stimulus reaches a critical angular size. Santer and colleagues (Santer et al, 2005) additionally demonstrated that the flying locust initiates a diving response that is correlated with the output of this neuron. Further, the time of DCMD's peak firing rate shows no dependency on stimulus texture, contrast or position (Gabbiani et al, 2001), consistent with the predictions of a perimeter detector model.…”
Section: Insights Into Underlying Neural Activitymentioning
confidence: 96%
“…They found that the DCMD neuron's peak spike rate occurs with a constant delay after the stimulus reaches a critical angular size. Santer and colleagues (Santer et al, 2005) additionally demonstrated that the flying locust initiates a diving response that is correlated with the output of this neuron. Further, the time of DCMD's peak firing rate shows no dependency on stimulus texture, contrast or position (Gabbiani et al, 2001), consistent with the predictions of a perimeter detector model.…”
Section: Insights Into Underlying Neural Activitymentioning
confidence: 96%
“…DCMD conveys the output of LGMD from the brain to interneurons and motoneurons involved in flight steering and jumping (Burrows and Rowell, 1973;Pearson et al, 1980;Simmons, 1980;Santer et al, 2005aSanter et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…As far as moment generation is concerned, it tried during this maneuver to generate nose-down pitching moment and roll towards the looming object as a mild decrease in roll indicates. Robertson and Reye [27] and later Santer et al [30] documented a similar response by Locusta migratoria, in which upon late detection of the looming object the locust straightened the wings up, stopped flapping for a short duration of about 0.3 s which would result in a quick loss of height and speed. They termed this maneuver a 'glide' and interpreted it as a last chance…”
Section: General Behavior Of a Light Locustmentioning
confidence: 88%
“…Their results also suggested that the DCMD could be better suited to predator evasion than avoiding obstacles in the animal's flight trajectory. Santer et al [30] recorded the steering movements and wing beat patterns of tethered migratory locusts in response to looming stimuli presented from the side, a situation that mimics attack from a predator. They observed a rapid stereotyped behavior, known as 'glide', in which the locust briefly ceases to flap its wings for about 200 ms and thereafter flaps its wings with increased frequency.…”
Section: Introductionmentioning
confidence: 99%